2019
DOI: 10.1111/psyp.13448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of native language experience on Mandarin lexical tone processing in proficient second language learners

Abstract: Learning the acoustic and phonological information in lexical tones is significant for learners of tonal languages. Although there is a wealth of knowledge from studies of second language (L2) tone learning, it remains unclear how L2 learners process acoustic versus phonological information differently depending on whether their first language (L1) is a tonal language. In the present study, we first examined proficient L2 learners of Mandarin with tonal and nontonal L1 in a behavioral experiment (identifying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 60 publications
(144 reference statements)
2
24
0
Order By: Relevance
“…In line with Näätänen et al (2004) and Pakarinen et al (2007) , the current study adopted a multifeature passive oddball paradigm, which consists of more than one type of deviant in one block ( Partanen et al, 2013 ; Yu et al, 2019 ). The 15 standard stimuli were played first to prompt participants to establish a standard perceptual template.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with Näätänen et al (2004) and Pakarinen et al (2007) , the current study adopted a multifeature passive oddball paradigm, which consists of more than one type of deviant in one block ( Partanen et al, 2013 ; Yu et al, 2019 ). The 15 standard stimuli were played first to prompt participants to establish a standard perceptual template.…”
Section: Methodsmentioning
confidence: 99%
“…Most of prior studies probed into lexical tones as a whole (e.g., Wang et al, 2001 ; Francis et al, 2003 ; Hallé et al, 2004 ), while more recent studies have switched to the dynamic interaction between acoustic and phonological information of lexical tones (e.g., Xi et al, 2010 ; Zhang et al, 2011 ; Yu et al, 2014 ). In general, the acoustic information consists of the physical features of lexical tones as estimated by F0 (e.g., pitch height and pitch contour), while the phonological information refers to the linguistic properties with tonal categories to distinguish lexical semantics ( Yu et al, 2019 ). Although some secondary cues might influence the judgment of lexical tone contrasts, F0 remains most critical as amply confirmed by the seminal ( Wang, 1976 ) and subsequent studies of categorical perception of lexical tones ( Xu et al, 2006 ; Peng et al, 2010 ; Shen and Froud, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there is a collection of wonderful studies on acoustic and phonological processing of lexical tones relating to hemispheric lateralization (Chapter 3 by Chao-Yang Lee and Seth Wiener, and Chapter 5 by Keke Yu, Ruiming Wang, and Ping Li). Divergent from prior studies examining lexical tone perception as a whole, the recently growing studies have shown that two types of information of lexical tones, namely acoustic information and phonological information, are processed differentially by our brain as evidenced by their respective neurophysiological correlates (Yu et al, 2019 ). Second, a heated debate has been discussed as regards the relationship between music and language (Chapter 8 by Jia Hoong Ong, Shen Hui Tan, Alice H. D. Chan, and Francis C. K. Wong).…”
mentioning
confidence: 89%
“…However, studies using mismatch negativity (MMN) paradigms have observed transfer based modulations of L2 tone perception. To this effect, only learners with a tonal L1 showed modulations of MMN effects based on tone functionality and not only pitch height (Shen & Froud, 2019; Yu, et al, 2019). For post-perceptive processing, no N400 for lexical tone mismatches or LAN/P600 for mismatches in grammar-related tone is found in natural L2 learners with a non-tonal L1 (Gosselke Berthelsen et al, 2020; Pelzl, Lau, Guo & DeKeyser, 2019).…”
Section: Introductionmentioning
confidence: 99%